PERAN BADAN USAHA MILIK DESA (BUMDes) SUMBER REJEKI DALAM PEMBERDAYAAN MASYARAKAT DESA RANTAU SAKTI DI KECAMATAN TAMBUSAI UTARA - Tengku Berlian (Fakultas Ekonomi Universitas Pasir Pengaraian, 2023)
Empowerment is a development process of society, by society and for society. As stated in Law no. 6 of 2014 concerning Villages article 1 paragraph 12 regarding the Empowerment of Village Communities is an effort to develop community independence and welfare byimprove knowledge, attitudes, skills, behavior, abilities, awareness, as well as utilize resources through establishing policies, programs, activities, and assistance that is in accordance with the essence of the problem and priority needs of the community village. BUMDes Sumber Rejeki is a business entity that is all or most of it the capital belongs to the village. It is hoped that the existence of BUMDes Sumber Rejeki can be achieved improve the community's economy. The aim of this research is to find out community empowerment process through the role of BUMDes Sumber Rejeki in Rantau village Sakti, North Tambusai sub-district, Rokan Hulu district and find out the factors what influences the role of BUMDes in empowering communities in Rantau Sakti village. The method used in this research is qualitative method with data collection techniques through observation, direct interviews, analysis interactively and takes place continuously through various stages including reduction, data presentation, verification and drawing conclusions. Research result shows that the role of the village-owned enterprise (BUMDes) Sumber Rejeki in community and opened several business units which is an absolute necessity community, including savings and loans, LPG gas stalls and clean drinking water businesses which are still running up to now and there are still some which are not yet running, namely Business clean drinking water. Until now, almost all of the programs are running well although not completely optimal.